Chloroalkylsulfonate ionic liquids by ring opening of sultones with organic chloride salts - Paape, Natalia; Wei, Wei; Bösmann, Andreas; Kolbeck, Claudia; Maier, Florian; Steinrück, Hans-Peter; Wasserscheid, Peter; Schulz, Peter (Chemical Communications, 2008)
An efficient route to prepare ionic liquids with chloroalkylsulfonate anions is presented; the synthesis proceeds in a one-step ring-opening reaction of sultones with an organic chloride salt and provides a very attractive access to new anion functionalised ionic liquids. © The Royal Society of Chemistry.